The Effect of Combined Training and Racing High-Speed Exercise History on Musculoskeletal Injuries in Thoroughbred Racehorses: A Systematic Review and Meta-Analysis of the Current Literature - Kylie L. Crawford; Benjamin J. Ahern; Nigel R. Perkins; Clive J. C. Phillips; Anna Finnane (Animals, 2020)
Despite over three decades of active research, musculoskeletal injuries (MSI) remain a global problem for the Thoroughbred (TB) racing industry. High-speed exercise history (HSEH) has been identified as an important risk factor for MSI. However, the nature of this relationship remains unclear, with an apparent protective effect of HSE against injury, before it becomes potentially harmful. Many MSI cases and fatalities occur during training rather than during racing, resulting in an underestimation of injury from studies focused on race day. The objective of this study was to examine the current evidence of the effect of combined training and racing HSEH on MSI in TB flat racehorses, through a systematic review and meta-analysis. A systematic search of the relevant literature was performed using PubMed®, Scopus®, Web of Science®, and Embase® online databases and the gray literature using sites containing “.edu” or “.edu.au”. Studies included in the review had explored seven different measures of HSE, including total career HSE distance, cumulative HSE distance in the 30 and 60 days before MSI, average HSE distance per day, per event and per 30 days, and the total number of HSE events. The total cumulative career HSE distance significantly affected the odds of MSI, with every 5-furlong increase, the odds of MSI increased by 2% (OR = 1.02; 95% CI 1.01, 1.03; p = 0.004). The average HSE distance per day also affected the odds of MSI, with every additional furlong increasing the odds of MSI by 73% (OR = 1.73; 95% CI 1.29, 2.31; p < 0.001). Other measures of HSE were not found to be consistently associated with risk of MSI, but these results should be interpreted with caution. Significant methodological limitations were identified and influence the comparability of studies. Standardizing the measures of HSE in studies of MSI, and describing training conditions in more detail, would support a more thorough investigation of the relationship between HSE and MSI. An improved understanding of this relationship is critical to mitigating the impact of MSI in the Thoroughbred racehorse.